The State-Owned Entities as Investors: The International Legal Framework - N. S. Andreeva (Теоретическая и прикладная юриспруденция)
In this article, the author examines the notion of state-owned entities in the practice of international organisations, and the different approaches to the extension of investor status to state-owned entities under international investment agreements. As a result of the analysis, the author formulates the characteristics of state-owned entities as investors in the international legal context and establishes that in the vast majority of cases state-owned entities are not excluded from the investor concept, and therefore shall be covered by the protection of international investment agreements.